Síntese de polímeros derivados de óleo de mamona com estireno e copolimerizados via radicais livres - Maia, Dayanne Lara Holanda (2019)
Castor oil can be used as precursor of new polymeric materials. Castor oil can be modified onto castor oil maleate (MACO) to present better reactivity towards polymerization. Castor oil maleate and styrene copolymers (MACO-Sty) were produced by suspension and bulk polymerization. Benzoyl peroxide (BPO) was used as free radical initiators in copolymerization. The effects of temperature (100 to 140 °C), molar ratio between styrene and castor oil maleate (2:1 to 4:1), and BPO concentration (0.10 to 0.20 wt%) were evaluated in both kinds of polymerization. The effects of water concentration (50 to 100%), and cobalt naphthenate concentration (0.10 to 0.20 wt%) were studied in the suspension and mass polymerization reaction, respectively. A factorial design was used to evaluate the effects of these variables on the number average molecular weight (Mn), weight average molecular weight (Mw) and dispersity (Đ). Viscosity of the resins, reaction yield and molar fraction of styrene in the copolymer were evaluated. A wide range of molecular weights (Mw from 15,809 to 38,656) could be produced, with dispersity ranging from 1.8 to 4.8. Copolymers with high yields (> 80%) and good thermal stabilities could be obtained. The results of biodegradation test showed that the synthesized materials have high biodegradability. Thus, adhesion tests in glass and waterproofing in wood indicated that MACO-St copolymers have the potential to be used as resins and adhesives.